2010
DOI: 10.1074/jbc.m109.040477
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C Inhibits Ribosomal RNA

Abstract: Mitomycin C (MMC) is a commonly used and extensively studied chemotherapeutic agent requiring biological reduction for activity. Damage to nuclear DNA is thought to be its primary mechanism of cell death. Due to a lack of evidence for significant MMC activation in the nucleus and for in vivo studies demonstrating the formation of MMC-DNA adducts, we chose to investigate alternative nucleic acid targets. Real-time reverse transcription-PCR was used to determine changes in mitochondrial gene expression induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 44 publications
0
33
0
4
Order By: Relevance
“…Proliferation of CD4+ T cells was determined as the dilution of CFSE signal using flow cytometry. For the contact dependent suppression assay, CD8+CD25 T cells induced from suboptimal stimulation with SEC1were treated with 10 μM of mitomycin C (Sigma-Aldrich) for 2 hours to prevent protein synthesis and proliferation (27, 28). After thorough washing, mitomycin C-treated CD8+CD25+ T cells were mixed with CFSE labeled responder cells and stimulated with anti-CD3/CD28 beads as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Proliferation of CD4+ T cells was determined as the dilution of CFSE signal using flow cytometry. For the contact dependent suppression assay, CD8+CD25 T cells induced from suboptimal stimulation with SEC1were treated with 10 μM of mitomycin C (Sigma-Aldrich) for 2 hours to prevent protein synthesis and proliferation (27, 28). After thorough washing, mitomycin C-treated CD8+CD25+ T cells were mixed with CFSE labeled responder cells and stimulated with anti-CD3/CD28 beads as described above.…”
Section: Methodsmentioning
confidence: 99%
“…27 Furthermore, mitomycin has been shown to also target rRNA, which may be another physiologically relevant cytotoxicity mechanism. 28 DNA alkylation by mitomycin takes place preferentially at the minor groove, as shown in Figure 6.9.…”
Section: Mitomycinsmentioning
confidence: 97%
“…33 The bioreductive alkylation process has been proposed to explain the interaction of mitomycin C with other nucleophilic biomolecules, providing additional mechanisms for its cytotoxicity. These nucleophiles include rRNA, 34 glutathione, 35 and thioredoxin reductase. 36 The proposed mechanism for the activation of mitomycin C to the active hydroquinone 6.2 by a dithiol is shown in Figure 6.11.…”
Section: Mitomycinsmentioning
confidence: 99%
“…For example, a recent study suggested the involvement of mitochondrial DNA damage in MMC activity. [30] The chemical transformations involved in MMC bioreduction and its reaction with DNA are well-established (Scheme 1). Under anaerobic conditions MMC can be reduced by a one-or two-electron process, and subsequent spontaneous loss of methanol leads to the formation of an unstable reactive intermediate hydroquinone.…”
Section: Cancer Drug Toxicity Control By Metabolic Enzymesmentioning
confidence: 99%